The Solutions of Diophantine Equation 1^4v_1^4+2^4v_2^4+3^4v_3^4+...+k^4v_k^4=1 - Muangkarn, Patchara; Janthasopha, Jakkraphan; Suanoom, Cholatis (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
In this paper, we introduce solutions of the Diophantine equation on the following from: where are positive integer such that and . The results show that there will be only 1 solution when , there will be only 3 solutions when , and there will be at least 4 partial solutions when .